Introduction to The Occurrence Process Rain through Project-Based Learning the Early-Age Child - Handayani, Ining; Katoningsih, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Early childhood science learning is one way to develop children's potential by applying the right learning model so that children can gain new knowledge from the results of observation, exploration, and experiments with various objects around during learning. The purpose of this study is the introduce the process of rain through Project-based Learning for early childhood. The subjects of this study were teachers and 20 children in class B1, while the object was the introduction of the process of rain. Primary Data is data obtained directly or data obtained from the first source through observation and interviews. While secondary data is data obtained indirectly in the form of photos and journals. This research method is descriptive qualitative research. Data collection techniques in this study are observation, interviews, and document studies. This observation activity is carried out through observation with children directly to obtain data for the study. Interviews were conducted with teachers and children. Documentation is carried out to obtain pictures or photos of the children studied. Data analysis techniques through data reduction are grouping, analyzing data that has been collected then presenting data is carried out by displaying the results that have been reduced, after the data is displayed then concluded. The results showed that the introduction of the process of rain through Project-based learning for early childhood can train children's cooperation, and increase activeness and creativity, children are directly involved in the experimental process so that understanding simple concepts of science in children's daily lives will be more optimal.